Sistem Informasi Akuntansi Penjualan Menggunakan MYOB Versi 18 Pada Toko Besi Puncak Jaya Stainless Karawang - Indaryono Indaryono; Arif Maulana Yusuf; Putri Purnamasari (Jurnal Accounting Information System (AIMS), 2023)
This writing aims to implement a sales accounting information system at the Puncak Jaya Stainless Cikarang iron shop which previously still used manual recording which resulted in frequent errors in recording data and stock items. The research methodology that the author uses consists of several stages starting with planning, data collection, data processing, and data migration to the MYOB Accounting Plus V18 application. The variable is the Sales Accounting Information System using the Mind Your own Business (MYOB) application version 18 which consists of Accounts, Banking, Sales, Purchases, Inventory and Card Files. This writing includes the type of descriptive writing. The data used are primary and secondary data, data collection techniques using interview and observation methods. The results of this writing show that to correct mistakes that occur in the company, an integrated system is needed to reduce and avoid mistakes, namely by implementing the Mind your own business (MYOB) V18 application which can make it easier to input data, can make it easier to search for data and information because the data is stored neatly. With the MYOB application, sales reports can be generated quickly and completely because transactions entered will be automatically journalized by myob, so that financial reports can be presented immediately and make decisions easier.